Agricultural Innovation in the Volta River Basin: An Analysis of Changes in Knowledge, Skills and Livelihoods brought about by the Volta Basin Development Challenge - Lasiter, Kalie; Tarrant, Anna (CGIAR Challenge Program on Water and Food, 2013)
Within the agricultural development sector, innovation has been identified as a primary pathway to achieve economic, social and environmental goals. Innovation is traditionally defined as a linear and relatively homogenous process involving the invention of a “new” technology that is then transferred and adopted by an intended user. However, recent definitions of innovation in agricultural development, most notably the Agricultural Innovation Systems (AIS) definition, describe innovation as a systemic process resulting from extensive knowledge networks, interactive learning, and negotiations among a heterogeneous set of actors. One way to create an innovation system (AIS) is through the formation and utilization of certain innovation configurations known as Multistakeholder Platforms (MSPs) and/or Innovation Platforms (IPs). CGIAR’s Challenge Programs on Water and Food (CPWF) use both MSPs and IPs to bring together a diverse set of relevant stakeholders to address common challenges in river basins globally, and in the Volta River Basin system in West Africa in particular. The Challenge Program’s Volta Basin Development Challenge Project (VBDC) focuses primarily on strengthening integrated management of rainwater and small reservoirs. The Emory graduate student research team worked in conjunction with the V5: Coordination and Change Project in order to investigate how/if the knowledge produced by V2-V4 projects in two regions in northern Ghana is contributing to innovative changes in villagers’ knowledge, skills and livelihood activities. This particular research is part of a broader Innovation Research Project for V5 that aims to identify the concurrent changes that have also taken place among V2, V3 and V4 project implementers. Specifically, the broader research will identify project researchers’ and technicians’ definitions of innovation i.e. what they consider innovations as a result of their interactions with project participants. Because agricultural innovation involves change not only at the community level, but at the organizational and institutional levels as well, understanding the motivations and justifications of implementing partners is therefore integral to assessing if and how agricultural innovation has occurred. Since this particular report is focused solely on the community level, it is difficult to ascertain the extent to which new practices and skills exhibited by community members are truly products of agricultural innovation systems. For the purposes of this report, therefore, innovation